Effect of microbial fertilizers and dosage of NPK on growth and yield of Upland Rice (Oryza sativa L.) - Fitriatin, Betty Natalie; Silpanus, Robi; Sofyan, Emma Trinurani; Yuniarti, Anni; Turmuktini, Tien (International Journal of Environment, Agriculture and Biotechnology, 2019)
Microbial fertilizers are inoculants made from beneficial microbes to improve soil nutrient availability and increase plant growth.The purpose of this research was to studythe effect of inoculants as microbial fertilizers (phosphate solubilizing microbes and Nitrogen-fixing bacteria) and NPK fertilizers on growth and yield of upland rice on Andisols. This experiment used a Randomized Block Design (RBD) in factorial pattern, consisting of two factors with three replications. The first factor consisted of inoculants, which were; without; inoculants A (Pseudomonas mallei, P. cepaceae, Aspergillusniger and Penicillium sp., Azotobacter sp., Azospirillum sp.); inoculantsB (Azotobacterchoroococum, A. viilandii, Azospirillum, Pseudomonas cepaceae, Penicillium and Acitenobacter) and inoculants A+B. The second factor were NPK fertilizers with four levels (100%, 75%, 50% and 25% dosage of recommendation). The results showed that microbial fertilizers improve growth and yield of upland rice.